Botswana : Selected Issues and Statistical Appendix. (IMF Staff Country Reports; Country Report ;, 2007)
This Selected Issues paper and Statistical Appendix on Botswana underlies that diamond reserves are not adequate to generate enough permanent revenue to support the current level of expenditure. Despite strong overall growth, in Botswana, a pattern of dependence on diamond revenue and high unemployment persists. Botswana, as a typical small open economy, is closely linked to a large neighboring economy. This linkage means Botswana's monetary and exchange policies must consider the external economic environment, particularly the pula's exchange rate against the rand.